Frataxin deficiency in neonatal rat ventricular myocytes targets mitochondria and lipid metabolism - Obis, Elia (2014)
Friedreich ataxia (FRDA) is a hereditary disease caused by deficient frataxin expression. This mitochondrial protein has been related to iron homeostasis, energy metabolism, and oxidative stress. Patients with FRDA experience neurologic alterations and cardiomyopathy, which is the leading cause of death. The specific effects of Frataxin depletion on cardiomyocytes are poorly understood because no appropriate cardiac cellular model is available to researchers. To address this research need, we present a model based on primary cultures of neonatal rat ventricular myocytes (NRVM) and shRNA interference. Using this approach, frataxin was reduced down to 5% to 30% of control protein levels after 7 days of transduction. At this stage the activity and amount of the iron-sulfur protein aconitase, in vitro activities of several OXPHOS components, levels of iron-regulated mRNAs or the ATP/ADP ratio were comparable to controls. However, NRVM exhibited markers of oxidative stress and a disorganized mitochondrial network with enlarged mitochondria. Lipids, the main energy source of heart cells, also underwent a clear metabolic change, indicated by the increased presence of lipid droplets and induction of medium-chain acyl-CoA dehydrogenase. These results indicate that mitochondria and lipid metabolism are primary targets of frataxin deficiency in NRVM. Therefore, they contribute to the understanding of cardiac-specific mechanisms occurring in FRDA and give clues for the design of cardiac specific treatment strategies for FRDA.